Neighbour effects on tree architecture: functional trade‐offs balancing crown competitiveness with wind resistance. (24th April 2017) - MacFarlane, David W.; Kane, Brian
Summary: The architecture of trees is the result of constrained, morphologically plastic growth – constrained by an underlying architectural model embedded in their genome, the structure of which can be significantly altered during growth to match the changing environmental conditions to which the tree is exposed. Here, we examined the hypothesis that crowding from neighbours should cause trees to optimize traits for light competition at the expense of wind resistance, with the reverse being true for trees lacking neighbours. Previous studies have examined the influence of light competition or wind resistance on shaping tree architecture, but few, if any, have simultaneously addressed trade‐offs for optimizing these traits in response to crowding from neighbouring trees in forests, as compared to open‐grown conditions. We studied the response of tree‐ and branch‐level architectural traits of temperate, broad‐leaved, deciduous tree species of differing shade tolerance and wood strength from multiple locations across the north‐eastern United States. Trees ranged in size (4–83 cm diameter at 1·3 m) and crowding conditions (open‐ and forest‐grown) and occupied different canopy positions. The open‐grown trees represented a null condition, where the lack of neighbouring trees to shape architectural traits could be contrasted with the influence of different levels of crowding in forests. Our results show strong evidence for a tree neighbourhood‐induced convergence of architectural traits across species and conditions, even when trees are growing in urban rather than natural forest conditions. After accounting for crowding, the effects of species and sample location contributed very little to explaining variation in architectural traits. One exception was crown dimensions, for which species‐specific differences explained about 15% of the residual variation. Under open‐grown conditions, alleviation of light competition caused trees to develop relatively large crowns and branches and a squat growth form suitable to resist greater wind exposure. By contrast, increasing shading from neighbouring trees caused forest‐grown trees to become increasingly more spindly in the main stem, with slender branches sparsely distributed over a disproportionately large crown volume – presumably to maximize light capture. Although the latter is an intrinsically less wind‐stable form, it can be adopted to increase light capture because neighbouring trees reduce exposure to the wind, which should greatly reduce the likelihood of stem breakage or uprooting under critical wind pressures. Alay summary is available for this article. Abstract : Lay Summary